2011
DOI: 10.1080/00140139.2011.606923
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elliptic handle shape on grasping strategies, grip force distribution, and twisting ability

Abstract: A generic torque model for various handle shapes has been developed and evaluated using experimental data. Twelve subjects performed maximum isometric torques using circular and elliptic cylinders in medium and large sizes (circular: r = 25.4, 38.1 mm; elliptic: semi-major/minor axes = 30.9/19.3, 47.1/27.8 mm) finished with aluminium and rubber, in two opposite directions. Torque, grip force distribution, and finger position were recorded. Maximum torques were 25%, 7%, and 31% greater for the elliptic, large-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…It has been also shown that rubber as tool-handle material increases the maximum torques from the hand to the handle [23]. This is due to greater frictional coupling between hand-handle interface.…”
Section: Introductionmentioning
confidence: 90%
“…It has been also shown that rubber as tool-handle material increases the maximum torques from the hand to the handle [23]. This is due to greater frictional coupling between hand-handle interface.…”
Section: Introductionmentioning
confidence: 90%
“…The importance of an ergonomic handle shape was explained by Kong et al (2008), Seo and Armstrong (2011) and Shih and Wang (1996), who concurred that a circular handle shape is unable to provide sufficient contact between fingers phalanges sectors and therefore would produce a lower total normal force as compared to an elliptic shape. Moreover, a larger normal force generation would lead to a larger frictional force and this notion prevents hand slippages and promotes a secure grip.…”
Section: Effect Of Ergonomics Features On Handle Gripmentioning
confidence: 99%
“…The comfortability of the elliptic handle shape was tested by Kong et al (2008), who found that it was the most comfortable shape among the other tested shapes. Seo and Armstrong (2011) and Gregor and Bojan (2014) also suggested that elliptic and anatomical shaped handles fit more comfortably in the hands. Hence, the handle with a more handaccommodating shape can help improve comfortability.…”
Section: Effect Of Ergonomics Features On Handle Comfortmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have researched the topic of tool handle design to define the optimal size and shape of a tool handle. Most of the studies have focused on cylindrical [5][6][7] or elliptical [8][9] shapes of the handles to provide guidelines for determining the optimal diameters to increase finger-force comfort, exertion, and the contact area. According to the previous studies on the related designs of the ergonomic handle, a hand tool design principles are summarized as following:…”
Section: Introductionmentioning
confidence: 99%